Impelementasi Metode Fuzzy Tahani Untuk Memilih Obyek Wisata Di Kota Makassar - Mallu, Satriawaty; Tandililing, Mika (LPPM- STMIK HANDAYANI MAKASSAR, 2016)
Makassar has a lot of potential tourist attractions that a tourist destination for tourists, each tourist has advantages and disadvantages which become the basis of consideration by every traveler in determining the sights you want to visit. It required a system that could allow potential travelers in determining the sights you want to visit. Design of decision support system for the selection of these sights using fuzzy tahani using three fuzzy variables, namely funding, distance, and time to visit is the choice of criteria by potential tourists, and decision support system is designed web-based so that it can be used by anyone who terkonekasi with Internet. Decision support system is expected to facilitate prospective tourists or sipengambil decision in selecting the sites you want to visit by potential tourists in accordance with the criteria chosen.